(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Role something institutional very needed in the activity process development for improve infrastructure development for the sake of prosperity life public and shift from country develop become country forward. Study this background by policy the economy is not optimal, uncertainty law and regulation, low power global competitiveness, lack inclusion finance, inclusion finance sharia, and inequality economy and social. Study This aim for analyze so far where role institutional for development in Indonesia towards shift development from country develop going to country forward. Method used in study this is use approach qualitative with use studies references and based on phenomenon that occurs. Results study this state that with development system institutional keep going optimized, policies push change from country develop going to country proceed become choice government. System finance sharia capable sustain strengthening economy society. Implications practical from this paper importance optimizing side of economic development and finance sharia for speed up change become country forward, and possible welfare enjoyed society.